Uso da aprendizagem colaborativa como ferramenta para avaliar anomalias craniofaciais sindrômicas - Bonan, Paulo; Lacerda, Rosa Helena; Muniz, Isis; Dantas, Eugênia; Silva, Daniel; Cavalcante, Bianca; Lavor, Juliane; Paulo, Júlia; Martelli Júnior, Hercílio; Vieira, Alexandre (Revista da ABENO, 2021)
Almost 30% of oral clefts are associated with other structural abnormalities. However, little is known on orofacial characteristics associated with these cases since they are not systematically reported. To close this gap, we developed a collaborative learning approach supported by an interprofessional team aiming to carefully describe oral findings and impact the training of future professionals that hopefully will incorporate these descriptions on their clinical practice. The methodological proposal consisted of small group sessions focusing on a particular syndrome or group of syndromes followed by the examination of patients with those conditions. Twenty cases were examined and studied over the course of one semester and a set of conditions to be identified in the orofacial region was defined. Here, we present a guideline that we suggest that dentists and dental institutions use. We also present the advantages of using collaborative learning as a tool in the training of the clinician.